KAJIAN NAUNGAN, TARAF PUPUK UREA DAN VARIETAS KEDELAI (Glycine max L.) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI SEBAGAI TANAMAN SELA DI AREAL PERTANAMAN KELAPA SAWIT MENGHASILKAN (Jurnal Online Pertanian Tropik, 2017)
The aims of this research were to analyze morpo_physiology changing of soybean under the oil palm area; determine the effect of shading and N fertilizer dosage on the growth and yield of soybean under the oil palm area, and determine suitable soybean varieties that enable grow and produce under oil palm. The experiment located in Ujung Labuan Village, Deli Serdang District. The experiment was arranged in Split-split Plot Design 3 x 4 x 3 with 3 replication, with three factors observed: 1) shade level, consist of: under 4 years old oil palm, under 6 years old oil palm, open area, 2) N dosage: 200 kg urea/ha, 150 kg/ha, 100 kg urea/ha, 0 kg urea/ha, 3) soybean variety: Anjasmoro, Burangrang, and Grobogan. Plant height, leaf area, plant dry weight, and soybean production were determined. The result showed there were some significant effects of interaction factors between oil-palm canopy shading, N dosage and soybean variety on growth and yield of soybean. The highest growth and production of soybean found in open areas. Between 4 years old oil palm and 6-7 years old oil palm, soybean growth, and production are insignificant different and lower than those on the opening area. N dosage makes some significant effects on growth and yield of soybean, which is usually nonsignificant between 150 kg Urea/ha or 200 kg Urea/ha. Meanwhile, soybean variety makes some significant effects. At the open area, burangrang make the highest growth and production by application of 200 kg urea/ha, but under oil palm, the highest production found at Burangrang under 4 years old oil palm and application of 200 kg urea/ha, followed by several treatments that are insignificantly different.